2013
DOI: 10.1111/hae.12107
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and ultrasound evaluation of “healthy” joints in young subjects with severe haemophilia A

Abstract: Magnetic resonance imaging (MRI) and ultrasonography (US) are increasingly used in haemophilia A (HA) to detect early joint changes. A total of 40 clinically asymptomatic joints, never involved by bleeding events ["healthy joints" (HJ)], were evaluated by MRI and, in parallel, by US in 20 young subjects with severe HA (22.45 ± 2.72 years old; no history of arthritides, of viral infections or of inhibitors against factor VIII). The same joints were evaluated in 20 matched non-haemophilic (no-HA) subjects (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
127
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(136 citation statements)
references
References 37 publications
7
127
1
Order By: Relevance
“…Sluiter et al evaluated 120 joints in 30 healthy adult men with frequent sports participation (≥4 times a week), and found no instances of abnormal IPSG MRI scores [5]. Similarly, Di Minno et al reported normal joint findings utilizing both ultrasound and MRI in their normal healthy volunteers [6]. Conversely, multiple groups have reported early structural joint changes in clinically asymptomatic joints of haemophilic males.…”
mentioning
confidence: 99%
“…Sluiter et al evaluated 120 joints in 30 healthy adult men with frequent sports participation (≥4 times a week), and found no instances of abnormal IPSG MRI scores [5]. Similarly, Di Minno et al reported normal joint findings utilizing both ultrasound and MRI in their normal healthy volunteers [6]. Conversely, multiple groups have reported early structural joint changes in clinically asymptomatic joints of haemophilic males.…”
mentioning
confidence: 99%
“…22 Subclinical microbleeds further contribute to the progressive development of target joints and subsequent complications, even among PwH on prophylaxis.…”
Section: Milestone 3 Freedom From Spontaneous Bleeds/ability To Enmentioning
confidence: 99%
“…,23 While prevalence TA B L E 1 Treatment model milestones of microbleeds is difficult to quantify, they are often suspected when joint abnormalities or damage is seen by MRI or ultrasound in the absence of clinically apparent bleeds. Strikingly, more than half of all asymptomatic joints show abnormal joint structure by MRI 22,24. In cases of cerebral microbleeds, detection methods are limited, and delays in diagnosis can lead to impaired cognition and hospitalization 25.…”
mentioning
confidence: 99%
“…Point-of-care ultrasound detection of affected joints -reliably correlating with magnetic resonance imaging detection of cartilage damage, effusion, and synovial hypertrophycarried out inside Hemophilia Centers at each patient's visit, could have major implications for the management of hemophilia patients. 46,47 Repeated evaluations of patients' joints will provide hints as to whether this strategy is worth the cost required.…”
Section: Identifying Newmentioning
confidence: 99%